LINGKAR LENGAN ATAS IBU HAMIIL AKAN MEMPENGARUHI PENINGKATAN BERAT BADAN BAYI LAHIR DI BPS ARTININGSIH SURABAYA - Kamariyah, Nurul; Musyarofah, Musyarofah (Jurnal Ilmiah Kesehatan, 2016)
the relationship of the upper arm circumference pregnant women with birth weight Artiningsih BPS Surabaya. Most women experience upper arm circumference is less than the normal limit . Based on preliminary data from 15 pregnant women found 10 women experience MUAC less than the normal limit . 5 women experience LILA normal limits . The purpose of analyzing the relationship of the upper arm circumference pregnant women with birth weight Artiningsih BPS Surabaya . This study uses an analytical method with cross sectional approach . Population is all mothers giving birth are recorded in BPS Artiningsih Surabaya by 33 respondents total sample of 30 respondents . Mechanical sampling probability sampling with simple random sampling . Using independent variable circumference of the upper arm , the dependent variable birth weight . The instrument uses secondary data then analyzed by Spearman Rank = 0.05 which means there is a connection upper arm circumference pregnant women with birth weight in BPS Artiningsih Surabay. The results showed 33 pregnant women most ( 66.7 % ) upper arm circumference is less , and most ( 54.1 % ) gave birth to babies with low birth weight , as well as the results of Spearman Rank p = 0.000 less than Conclusions LILA increasingly normal pregnant women increasingly gained normal birth weight . expected to pregnant women who have a MUAC <23.5 cm were able to increase the consumption of better nutrition.